ASME 2016 Internal Combustion Engine Division Fall Technical Conference 2016
DOI: 10.1115/icef2016-9367
|View full text |Cite
|
Sign up to set email alerts
|

The Combustion and Emissions Performance of a Syngas-Diesel Dual Fuel Compression Ignition Engine

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…But the use of syngas in IC engines nowadays has to be optimized, considering both efficiency (to limit the carbon footprint) and the exhaust emissions. Nonetheless, research on the characteristics of syngas fueled IC engines is limited [5,6,7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…But the use of syngas in IC engines nowadays has to be optimized, considering both efficiency (to limit the carbon footprint) and the exhaust emissions. Nonetheless, research on the characteristics of syngas fueled IC engines is limited [5,6,7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Their results revealed that the rate of direct injection fuel was higher at maximum engine loads than at lower loads, so the engine performance should be lower than the full load to minimize diesel intake. Guo et al 22 focused on specifying the effects of syngas and diesel in a dual-fuel engine for different compositions of syngas on achieving lower thermal efficiencies for the dualfuel mode. Because H 2 and CO fuels do not emit soot, diesel was responsible for the soot emission.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations have also been carried out to study the effect of syngas substitution of fossil diesel on the performance of diesel-syngas dual-fuel Reactivity Controlled Compression Ignition (RCCI) engines [8][9][10][11][12]. Rith et al [8] and Kousheshi et al [9] utilised real syngas in their investigations while Mahgoub et al [10], Guo et al [11] and Olanrewaju et al [12] utilised simulated syngas in their investigations. These works confirm the feasibility of the use of diesel-syngas dual fuel in RCCI engines for power generation.…”
mentioning
confidence: 99%